Contribuições da ética do cuidado para uma concepção holística de educação - Milêu, Vanessa Mattos Magalhães (2021)
The main objective of the dissertation is to conceptualize and list the possible contributions of Holistic Education in/for educational practice, linking the idea presented by researcher and philosopher Leonardo Boff in relation to the Ethics of Care. We opted for a qualitative research, addressing characteristics as well as the contributions of this educational proposal, carried out through bibliographical analysis, reflections, hypotheses, questioning, all in order to answer the following research problem: what are the contributions of Holistic Education and the Ethics of Care in contexts involving the teaching-learning process? Therefore, the present work presents reflections that seek to contemplate the foreseen objectives: to approach the chosen theme through Integral Education, Holistic Education, Legislation and the Ethics of Care, conceptualize Holistic Education, carry out a brief survey of Brazilian legislation interrelating it with Holistic Education, in addition to scrutinizing and presenting some reflections based on Boff's knowledge production. In this way, the relevance of this research is justified, since the intention is to unravel and discover if the theme presents can contribute and answer some of the concerns that arise during the educational process. As a final product, we highlight the creation of an Informative Online Booklet addressing the theme involving this educational proposal.